Health Officer Support For Regulation of Iron Tablets Consumption During Pregnancy - Yuni Purwati; Nur Aini Rustiana Dewi (International Journal of Science, Technology & Management, 2021)
The obedience in consuming iron tablets had a good effect for the pregnant women. It is because iron tablets were able to increase the nutritional intake for the fetus, prevent anemia (iron deficiency), prevent bleeding during childbirth, and reduce the death risk. The supports of the health workers were expected to improve the The obedience of the pregnant women in consuming the iron tablets. The objective of this research was to find out the effect of the supports of the health workers and the obedience of the pregnant women in consuming the iron tablets at Sewon II Public Health Center, Bantul Regency, Yogyakarta Province. The method used in this study was through the descriptive correlation using a cross-sectional approach. The sampling technique used in this study was through the total sampling. The number of the respondents of this study was 80 respondents. The data analysis technique used in this study was the Kendall tau. The result of this data analysis showed that the p-value of 0.000 < 0.05. It meant that there was a significant correlation between the two variables of this study. Moreover, the significant correlation between the support of the health workers and the obedience of the pregnant women in consuming the iron tablets is in the moderate level (0.549). Therefore, it was concluded that the health workers were expected to improve the information supports, the appreciation supports, the instrument supports, and the emotional supports so that the pregnant women were able to consume the iron tablets.